124k views
4 votes
-2x + 5y = -4
3x + 4y = -17

Use elimination to solve

User MFarmer
by
5.2k points

2 Answers

5 votes

the answer is x=-3 y=-2. you need to download photomath app to solve every equation you want

User J Avery
by
6.2k points
6 votes

Answer:

(- 3, - 2 )

Explanation:

Given the 2 equations

- 2x + 5y = - 4 → (1)

3x + 4y = - 17 → (2)

Multiplying (1) by 3 and (2) by 2 and adding the result will eliminate x

- 6x + 15y = - 12 → (3)

6x + 8y = - 34 → (4)

Add (3) and (4) term by term

(- 6x + 6x) + (15y + 8y) = (- 12 - 34), that is

23y = - 46 ( divide both sides by 23 )

y = - 2

Substitute y = - 2 in either of the 2 equations.

Substituting in (2)

3x - 8 = - 17 ( add 8 to both sides )

3x = - 9 ( divide both sides by 3 )

x = - 3

Solution is (- 3, - 2 )

User Washington
by
5.1k points